Analisis peran motivasi berprestasi dalam keterampilan pemecahan masalah pada siswa laki-laki dan perempuan di SD - Zahra Nurmayusanti; Ani Nur Aeni; Rana Gustian Nugaraha (Indonesian Journal of Learning and Educational Studies, 2026)
This study aims to analyze the role of achievement motivation in problem-solving skills among male and female elementary school students. A descriptive qualitative method was applied with six fifth-grade students from SDN Rancapurut as participants, consisting of three males and three females. Data were obtained through problem-solving tests, interviews, and documentation, then analyzed thematically using Nvivo software. The findings indicate that female students tend to be more detailed and systematic in understanding and planning solutions, while male students are more efficient and pragmatic in execution. Achievement motivation serves as a key factor influencing students’ persistence and consistency across problem-solving stages.